English English - Hibatun Naeem; Ignatius Oki Dewa Brata (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
Trends regarding Sustainability Reporting in Indonesia are experiencing positive developments. It can be concluded that the company already has an awareness that the company's survival depends on the company's relationship with the environment. This follows the legitimacy theory which states that the company has a contract with the community to carry out its activities based on the values ​​of justice and how the company responds to various interest groups to legitimizing company actions. In this research, researchers aspire to analyze which was more effectively trigger an effect on the development of an upward trend in Sustainability Reporting. From several samples taken, researchers obtained data that represent financial performance and company size. After being processed using logistic regression, it was found that the size of the company had the most effect on the disclosure of the Sustainability Report.